Colder temperatures augment viability of an indirectly transmitted songbird pathogen on bird feeders - Sara R. Teemer; Edan R. Tulman; Alicia G. Arneson; Steven J. Geary; Dana M. Hawley (Ecosphere)
Abstract Inanimate surfaces that are contaminated with infectious pathogens are common sources of spread for many communicable diseases. Understanding how ambient temperature alters the ability of pathogens to remain viable on these surfaces is critical for understanding how fomites can contribute to seasonal patterns of disease outbreaks. House finches (Haemorhous mexicanus) experience fall and winter outbreaks of mycoplasmal conjunctivitis, caused by the bacterial pathogen Mycoplasma gallisepticum (MG). Although bird feeder surfaces serve as an indirect route of MG transmission between sick and healthy individuals, the contributions of feeders to MG transmission in the wild will depend on how ambient temperature affects viability and pathogenicity of MG on feeder surfaces over time. Here, we used two experiments, with identical initial design, to assess such temperature effects. For both experiments, we pipetted equal amounts of MG onto replicate feeder ports held at night‐day temperatures representing summer (22–27°C) or winter (4–9°C). We allowed MG to incubate on feeders at either temperature and swabbed remaining inocula from surfaces at 0, 1, 2, 4, or 7 days post‐inoculation of the feeder, with each replicate feeder port only swabbed at a single time point. In the first study, we analyzed swabs using a culture‐based assay and found that MG incubated at colder versus warmer temperatures maintained higher viability on feeder surfaces over time. In the second study, we replicated the same experimental design but used MG swabs from feeder surfaces to inoculate wild‐caught, pathogen‐naïve birds and measured resulting disease severity and pathogen loads to determine pathogenicity. We found that MG remained pathogenic on feeder surfaces at cold ambient temperatures for up to one week, much longer than previously documented. Further, MG was significantly more pathogenic when incubated on feeders in colder versus warmer temperatures, with the strongest effects of temperature present after at least four days of incubation on feeder surfaces. Overall, cold ambient temperatures appear to alter the role of fomites in the MG transmission process, and temperature likely contributes to seasonal disease dynamics in this system and many others.